Continuous synergy between UMP and ECERDC helped boost academic achievement of students in rural area - UMP, PNC
In a move to strike a balance in the growth of rural and urban areas, collaborations between institutes of higher learning (IPTS), government agencies, industries and regional economic development councils can improve the socio-economic development of local community including students' academic achievement.